THE INFLUENCE OF SOCIAL NETWORKS ON THE SPIRITUAL IMAGE OF THE INDIVIDUAL - Ravshan Nazarov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article analyzes the views formed on the importance of the impact of social networks on the spiritual image of the individual today and the main views and differences that are unique.